Correlation between testicular volume and histological findings in children with unilateral cryptorchidism: Potential impact on future fertility. Issue 2 (May 2022) - Spinelli, Claudio; Morelli, Girolamo; Cito, Gianmartin; Bertocchini, Alessia; Ghionzoli, Marco; Pucci, Angela; Cocci, Andrea; Morganti, Riccardo; Strambi, Silvia
Objectives: Our aim is to assess the correlation between testicular volume and histological findings in children with unilateral cryptorchidism. Methods: From September 2016 to August 2018, from 60 patients surgically treated for cryptorchidism, 45 children were enrolled in this single-center prospective study. Depending on the degree of testicular volume reduction, patients were divided into Group 1 with <20% reduction and Group 2 with reduction ⩾20%. Patients underwent unilateral orchidopexy and simultaneous biopsy of the undescended testis. Tanner stage was assigned. Tubular Fertility Index was measured. Results: Group 1 included 20 patients (44.4%) and Group 2 included 25 patients (55.5%). Mean age was 2.10 years (range 12 months–3.8 years) in Group 1 and 2.8 years (range 18 months–4.41 years) in Group 2. Although there is a positive correlation between testicular volume and Tubular Fertility Index, no significant association was found between groups ( p -value = 0.29). Furthermore, histological patterns did not differ significantly among groups. Conclusions: The degree of volume reduction in undescended testis does not seem to correlate significantly with the severity of histological changes that accompany cryptorchidism. Tubular Fertility Index could serve as objective tool for the assessment of future fertility.